1989
DOI: 10.1111/j.1939-0025.1989.tb01635.x
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal behavior in "normal" adolescents: Risk and protective factors.

Abstract: Risk and protective factors were examined in suicidal and nonsuicidal public high school students. With life stress and depression as independent risk factors, family cohesion was found to offset the effect of stress, and friendships to have c more indirect effect. Differential effects of ten sources of stress were analyzed from a developmental perspective, and the probability of suicidal behavior associated with clusters of factors was estimated for the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
103
2
3

Year Published

1991
1991
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(115 citation statements)
references
References 13 publications
7
103
2
3
Order By: Relevance
“…There is evidence that the families of adolescent self-harmers are disorganized (Friedrich et al, 1982;Meneese & Yutrzenka, 1990), with poor cohesion (Asarnow, 1992;Asarnow et al, 1987;Brent et al, 1990;Friedrich et al, 1982;Garrison et al, 1991;Rubenstein et al, 1989) and prone to domestic violence (Cohen-Sandler et al, 1982). Poor communication (Tulloch et al, 1997), over-protectiveness Martin et al, 1995) and lack of nurturance (Fotti et al, 2006;Stewart et al, 1999;Wagner et al, 1995) have also been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that the families of adolescent self-harmers are disorganized (Friedrich et al, 1982;Meneese & Yutrzenka, 1990), with poor cohesion (Asarnow, 1992;Asarnow et al, 1987;Brent et al, 1990;Friedrich et al, 1982;Garrison et al, 1991;Rubenstein et al, 1989) and prone to domestic violence (Cohen-Sandler et al, 1982). Poor communication (Tulloch et al, 1997), over-protectiveness Martin et al, 1995) and lack of nurturance (Fotti et al, 2006;Stewart et al, 1999;Wagner et al, 1995) have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, suicidal adolescents are more likely to live in nonintact families compared with non-suicidal peers (De Wilde et al, 1992;Kienhorst et al, 1990;Paluszny et al, 1991). When young people do live with their parents, there may be poor attachment (Adam, 1994;Adam et al, 1996;Lessard & Moretti, 1998;Martin & Waite, 1994), parent -child confl ict (Asarnow, 1992;Brent et al, 1990;Meneese & Yutrzenka, 1990;Rubenstein et al, 1989), hostility (Kosky et al, 1986) and rejection (Fotti et al, 2006). Moreover, family confl icts are among the most commonly identifi ed precipitants to self-harm, based on adolescent self-report (Lowenstein, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Protective aspects of interpersonal skills have been indicated by empirical studies (Leadbeater, Hellner, Allen, & Aber, 1989; Pellegrini, 1980;Rubenstein, Heeren, Housman, Rubin, & Stechler, 1989) as well as by clinical case discussions of resilient children. Such children have been described as having high social skills (e.g., Masten et al, in press), with characteristics such as warmth, spontaneity, and expressiveness (Murphy & Moriarty, 1976).…”
Section: Nih Public Accessmentioning
confidence: 99%
“…In earlier studies on preadolescents, intellectual ability has been found to be protective against stress in predicting various indices of competence (Masten et al, 1988; Pellegrini, 1980). Similarly, Werner and Smith (1982) found that during young adulthood, resilient individuals had high faith in their own control over their environment (reflecting an internal locus of control) as opposed to believing that the external environment was determinative.Protective aspects of interpersonal skills have been indicated by empirical studies (Leadbeater, Hellner, Allen, & Aber, 1989; Pellegrini, 1980;Rubenstein, Heeren, Housman, Rubin, & Stechler, 1989) as well as by clinical case discussions of resilient children. Such children have been described as having high social skills (e.g., Masten et al, in press), with characteristics such as warmth, spontaneity, and expressiveness (Murphy & Moriarty, 1976).…”
mentioning
confidence: 99%
“…Dette understøttes også av forskning innen det suicidologiske feltet. Opplevelse av samhold og støtte fra familien beskytter mot både selvmordstanker og -forsøk i ungdomsårene (Rubenstein et al 1989). Og støtte fra ektefelle eller annen naer fortrolig er den viktigste beskyttende faktor under større livspå-kjenninger og kriser.…”
Section: Familien Som Ressursunclassified